PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN MUSI RAWAS - Rudi Azhar (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2019)
This study entitled The Effect of Motivation and Work Environment on Employee Performance at the Environmental Service of Musi Rawas Regency. The objectives to be achieved in this study were to determine the effect of motivation and work environment on employee performance at the Environmental Service of Musi Rawas Regency. Thepopulation in this study were all employees who worked in the  nvironmental Office of Musi Rawas Regency, totaling 51 people. Data collection techniques in writing this use observation, documentation and questionnaire. The analysis technique uses simple regression analysis, correlation test, t test, multiple linear regression, determinationtest, and f test. Based on the analysis and discussion it can be concluded that 1) there is the effect of motivation on employee performance at the Environmental Service of Musi Rawas Regency, where the results of simple linear regression Y = 56,430 + 0,492 Motivation, correlation coefficient value of R=0,434 and t-test value of t = 3,370 > t table = 2,009. 2) There is an Influence of the Work Environment on Employee Performance in the Environmental Service of Musi Rawas Regency. which obtained the results of a simple linear regression test Y = 55,980 + 0,431 Work Environment, the correlation coefficient value of R=0.522 and t-test value of t count = 4,288 > t table = 2.009. 3) There is a Motivation and Work Environment Effect on Employee Performance at the Musi Rawas District Environmental Service, where the results of multiple linear regression Y = 41,828 + 0,318 X1 + 0,346 X2, the determination coefficient value R2=0,584 and the Fcount obtained is =12,400>Ftable=3,19.Keywords: Motivation, Work Environment, Performance